Development of Bilayer Biodegradable Composites Containing Cellulose Nanocrystals with Antioxidant Properties - Galotto-Lopez, M; Rojas-Sepulveda, A; Lopez de Dicastillo-Bergamo, A; Velasquez, E (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
The interest in the development of novel biodegradable composites has increased over last years, and multilayer composites allow the design of materials with functionality and improved properties. In this work, bilayer structures based on a coated zein layer containing quercetin and cellulose nanocrystals (CNC) over an extruded poly(lactic acid) (PLA) layer were developed and characterized. Bilayer composites were successfully obtained and presented a total thickness of approx. 90 m. The coated zein layer and quercetin gave a yellowish tone to the composites. The incorporation of the zein layer containing CNC decreased the volatile release rate during thermal degradation. Regarding to mechanical properties, bilayer composites presented lower brittleness and greater ductility evidenced by a lower Young s modulus and higher elongation values. Water permeability values of bilayer composites greatly increased with humidity and the zein coated layer containing quercetin increased this effect. Experimental data of quercetin release kinetics from bilayer structures indicated a higher release for an alcoholic food system, and the incorporation of cellulose nanocrystals did not influence the quercetin diffusion process. © 2019 by the authors.
Keywords: poly(acid lactic); bilayer; zein; active packaging; quercetin; cellulose nanocrystals